Smart Air Filtration Systems for Cities: A Technological Approach to Reducing Urban Pollution - Ravikant Nanwatkar; Om Dhawale; Rushikesh Bari; Adesh Jagtap (International Journal of Environmental Noise and Pollution Control, 2024)
Urban air pollution is considered one of the main ecologically critical issues of the 21st century since it threatens citizens' health through respiratory diseases, pathologies of the cardiovascular system, and even premature death. Regarding an extremely high level of pollution in large cities, it becomes necessary to realize technological solutions which could avoid the negative impact of this phenomenon. Smart air filtration systems have emerged as promising solutions for urban pollution by leveraging cutting-edge technologies like the Internet of Things, AI, adaptive filtration mechanisms, and real-time monitoring. Advanced systems today dynamically adjust to changed levels of pollution by offering real-time air quality improvements through intelligent response mechanisms that further optimize filtration processes based on immediate environmental data. Integration of IoT sensors for pollution monitoring, combined with predictive modelling using AI algorithms, allows the filtration solutions to work autonomously, further increasing their efficiency and scalability across bigger urban areas. The following report will review the technological basis, efficacy, challenges, and scaling of smart air filtration systems in the context of their potential contribution to reducing urban pollution and improving public health outcomes. Case studies of various cities around the world further illustrate the real-world applications of how the successful implementation of smart filtration systems has been done to address air pollution. The report also explores policy frameworks that need to be laid down to ensure wide-scale adoption of such systems, taking an overview of economic, social, and environmental concerns. The aim of this analysis is to inform city planners, policymakers, and environmental advocates about the role that advanced air filtration technologies can play in fostering cleaner, healthier urban environments.
Keywords: Artificial Intelligence-AI; Case Studies; Internet of Things-IoT; Predictive Modelling; Real-time Data; Scalability; Urban air pollution; adaptive filtration; air quality improvement; and pollution mitigation strategies; autonomous operation; environmental technology; management of urban air quality; policy frameworks; pollution monitoring; smart air filtration systems; urban health